ANALYSIS OF THE RELATIONSHIP BETWEEN COOPERATION INTENSITY AND EXPORT PERFORMANCE: A TAXONOMIC PROPOSAL - Fabrini, Adriana Gresielly; Limas, Cesar Eduardo Abud (Gestão e Desenvolvimento em Revista, 2020)
This study identifies three distinct levels of cooperation among Brazilian exporting companies and explores how cooperation intensity is related to export performance. Through a cluster analysis, a three-level taxonomy was proposed for inter-organizational cooperation. Data were collected for 157 Brazilian exporting companies, in January–February, 2018, the Qui-Square test show the findings reached can be extended to the population. The results state the more intense the asset sharing with other companies, higher the export performance. It was found that there is an increase of approximately 13% in export performance when the number of assets shared increase from 2 to 8.